MOTIF SYEKHERMANIA MENGAKSES VIDEO DAKWAH HABIB SYECH BIN ABDUL QODIR ASSEGAF - Uwes Fatoni; Eka Octalia Indah Librianti (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
The purpose of this study is to determine the motives and needs of the audience in accessing and watching video preaching Habib Syech bin Abdul Qodir Assegaf on youtube social media. This research uses primary data that is data obtained from Habib Syech bin Abdul Qodir Assegaf or so-called Syekhermania as key informant and information obtained through interview. The type of this research is descriptive qualitative research. The result of this research is known that the motives of syekhermania in accessing video of Da'wah Habib Syech through youtube have the aspect of need that is curiosity about information, the need for an entertainment which found in accessing youtube, the need of its nature to make the muballigh as an example in its life, the need to socialize with the community and the last is the need that just want to get away from various problems.